'Doing fifty-five in a fifty-four': Hip hop, cop voice and the cadence of white supremacy in the United States. Issue 2 (1st November 2018) - Stoever, Jennifer Lynn
This article examines how police officers in the United States use a racialized and gendered way of speaking called 'cop voice' to provoke fear and extreme forms of compliance from people of colour. Through autoethnographic analysis coupled with sonic attention to how Jay-Z ('99 Problems'), Public Enemy ('Get the Fuck Out of Dodge') and Prince Paul ('The Men in Blue') represent 'cop voice' through shifts in their rapping flow or by using white guest rappers, 'Doing 55 in a 54' argues that police weaponize their voices. Identifying and listening closely to these examples of cop voice reveal how people who are raced as 'white' in the United States mobilize this subject position in their voices through particular cadences that audibly signify racial authority, while at the same time, never hearing themselves as doing so.